Evolução da bovinocultura de corte no Mato Grosso e o uso de grãos de destilaria do milho em confinamento - Andrade, Thiago Sérgio de (2023)
The state of Mato Grosso (MT), a key player in the Brazilian agribusiness, has been driving impactful transformations in its livestock industry over the years, unveiling a dynamic and adaptive profile. This focus is delineated in the first chapter of this analysis. The acquisition of data from the Instituto de Economia e Estatística (IMEA), the Instituto de Defesa Agropecuária (INDEA) and Instituto Brasileiro de Geografia e Estatística (IBGE) of MT, has enabled a comprehensive understanding of this scenario. With prominence in meat production in the country since 2006, the state has expanded its contribution to the national slaughter from 7.30% to 14.59% in 2021. Simultaneously, the average carcass weight has increased by approximately 24.24 kg over this period, accompanied by substantial seasonal changes in slaughter patterns. Formerly concentrated during the rainy season, slaughter now occurs in greater proportion during the dry season. A noteworthy aspect is the modification in the age of slaughtered animals. The proportion of animals aged over 36 months in slaughter has remarkably decreased, from 48.28% in 2008 to 9.05% in 2022. In contrast, the slaughter of animals aged between 1 and 2 years has shown a remarkable increase, rising from 2.72% to 24.28% during the same interval. Concurrently, the ratio between young and older animal slaughter has approached a 1:1 equilibrium, irrespective of the month. The transition towards earlier slaughter, coupled with the increase in carcass weight, reflects a commitment to producing high-quality meat that meets the demands of the domestic market and international expectations. In the second chapter, the focus shifts to the inclusion of corn distillers' grains (CDG) in the diet of feedlot cattle, a pertinent topic for Mato Grosso. Presently hosting 11 out of 20 corn ethanol plants in Brazil, this evaluation is critical. While a broad international literature discusses the use of CDG in North America, it is imperative to acknowledge the nuances of corn ethanol production processes in the central Brazilian context. Based on a meta-analysis, the study delves into the effects of CDG usage on the performance of feedlot cattle in the country, considering variables such as growth, digestibility, and ruminal fermentation. Results indicate that the inclusion of CDG in the diet did not exert a significant impact (p > 0.05) on performance variables, including dry matter intake, average daily gain, final weight, and feed efficiency. However, carcass characteristics were affected (p ≤ 0.05), with a 6.28 kg increase in hot carcass weight, as well as increments in ribeye area by 0.1806 cm² and backfat thickness by 0.5479 mm. Concerning ruminal fermentation, an impact on the molar proportion of butyric and valeric acid was observed, although ruminal pH remained unaffected.These analyses underscore the dynamic transformations in both federal and state livestock industries, such as CDG, in Brazil. They demonstrate the sector's commitment to enhancing meat quality and production efficiency in a sustainable manner, aligned with the demands of the global market.